2017
DOI: 10.1590/0366-69132017633651964
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de planejamento experimental no estudo para imobilização de lodo galvânico em cerâmica vermelha para minimização de impactos ambientais

Abstract: ResumoO trabalho proposto tem como objetivo avaliar por meio de planejamento estatístico a incorporação de um resíduo de galvanoplastia (lodo com metais altamente poluidores, como o cromo) em cerâmica vermelha, para a redução em seu armazenamento e a diminuição de sua contaminação ao meio ambiente e ao homem. Para isso, o lodo galvânico e a argila utilizada foram caracterizados quanto à densidade, caracterização visual, pH, umidade, matéria orgânica total, quantidade de cromo presente, espectroscopia de infrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…However, the emergence of stricter regulations in order to slow down the exploitation of non-renewable natural resources has motivated the use of waste materials as high-quality raw materials [4,6]. The use of wastes, after detecting their potential, contributes to product diversification, energy savings, and improvement in population health [7][8][9][10][11]. In recent years, several studies have demonstrated the feasibility of using industrial waste in the manufacture of ceramic products, especially porous ceramic products.…”
Section: Introductionmentioning
confidence: 99%
“…However, the emergence of stricter regulations in order to slow down the exploitation of non-renewable natural resources has motivated the use of waste materials as high-quality raw materials [4,6]. The use of wastes, after detecting their potential, contributes to product diversification, energy savings, and improvement in population health [7][8][9][10][11]. In recent years, several studies have demonstrated the feasibility of using industrial waste in the manufacture of ceramic products, especially porous ceramic products.…”
Section: Introductionmentioning
confidence: 99%
“…In the ceramics manufacture, the sintering or burning stage to which we submit the mass is given by the transformations carried out with the use of thermal energy, in which the removing process of the remaining moisture from the drying phase occurs. Sintering is an irreversible process, in which flaws committed in previous steps become clear [16]. For red ceramic materials manufacture, we used temperatures around 950°C [17].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the evolution of environmental laws related to mining activities and the production of building materials, the use of alternative raw materials has become an important sustainable option for reducing the consumption of natural resources. Chamote, steel slag and sand from metallurgical foundries, demolition waste, textile industry slurry and sludge from water treatment and electroplating plants are alternative raw materials coming from widely used industrial processes . Sludge, for example, is a waste material, which originates from water treatment plants (WTP) or effluent treatment plants (ETP).…”
Section: Introductionmentioning
confidence: 99%